2003
DOI: 10.3748/wjg.v9.i2.381
|View full text |Cite
|
Sign up to set email alerts
|

One-stage urethral reconstruction using colonic mucosa graft: an experimental and clinical study

Abstract: Urethral mucosa can be replaced by colonic mucosa without damaging the continence mechanism in female dogs. Colonic mucosa graft urethral substitution is a feasible procedure for the treatment of complex urethral stricture of a long segment. The technique may be considered when more conventional options have failed or are contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Complications, such as graft necrosis, meatal stenosis, stricture, and fistula formation, are common in these procedures. Furthermore, some recent research using small intestine or colon mucosa for urethral reconstruction have shown good results [5][6][7]. However, in spite of satisfying reconstruction outcomes in the patients, they are subjected to potential complications of abdominal surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Complications, such as graft necrosis, meatal stenosis, stricture, and fistula formation, are common in these procedures. Furthermore, some recent research using small intestine or colon mucosa for urethral reconstruction have shown good results [5][6][7]. However, in spite of satisfying reconstruction outcomes in the patients, they are subjected to potential complications of abdominal surgery.…”
Section: Discussionmentioning
confidence: 98%
“…[1] Reports show that split and full-thickness skin grafts from the scrotum, penis and extragenital sites (ureter, saphenous vein, appendix, colonic mucosa, medial upper arm, neck, lateral chest and abdomen), bladder mucosa and, more recently, oral mucosa have been used. [2][3][4][5][6] Skin provides abundant material that is easy to harvest, but its keratinized epithelium and split-thickness depth increase susceptibility to postoperative contracture, stricture formation and graft thickening when tabularized. [6] The skin hair also constitutes a major problem when hairy skin is used as a graft for urethral reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Urethral substitution with intestinal segment has been used in congenital urethral anomalies [24,25]. Experimental use of colonic graft has also been reported [26]. Our experience shows that nearly 60% of recurrent strictures in children cannot be managed by anastomotic urethroplasty ( Table 2).…”
Section: Redo Casesmentioning
confidence: 67%